The effect of different salinity on egg hatchability and survival of tiger grouper larvae (Epinephelus fuscoguttatus) - Purba, Ivrado; Febri, Suri Purnama; Komariyah, Siti; Nasution, Lucky Marzuki; Rusyani, Emy; Nazlia, Suraiya (Universitas Malikussaleh, 2024)
This study aims to analyze the effect of different salinity on egg hatchability and survival of tiger grouper larvae (Epinephelus fuscoguttatus). The method used in this study was an experimental method with 4 treatments repeated 3 times. Each treatment was given a different salinity P1= 30 ppt, P2= 25 ppt, P3= 20 ppt, P4= 15 ppt. The results of giving different salinity treatments had a significant effect (P <0.05) on egg hatchability and survival of tiger grouper larvae. The results showed that the best salinity treatment for egg hatchability and survival of tiger grouper larvae was in the P1 treatment (30 ppt) with values of 40.96 ± 0.24d, and 84.41 ± 0.89c. Thus, hatching of eggs and hatching of tiger grouper larvae should be done at a salinity of 30 ppt.Keywords: Egg Hatch Rate; Salinity; Survival; Tiger Grouper